Application of an adaptive algorithm to the control of the plasma vertical position - Scibile, L; Kouvaritakis, B (ANS, 1999)
A novel nonlinear controller for the vertical position based on a discrete adaptive near-time optimum control algorithm (DANTOC) is used to stabilize the tokamak system, to maximize the stability region, and to provide robustness with respect to the sources of disturbances and measurement noise. The controller is tested in simulation for the Joint European Torus tokamak, and the results demonstrate its feasibility in controlling the vertical position for different plasma configurations. The controller is also tested on the COMPASS-D tokamak. The results demonstrate the improvement with respect to a simple linear proportional and derivative controller in the presence of disturbances and measurement noise.